Relevansi Filsafat Ilmu dan Bahasa - Sri Rahayu, Maya; Saadah , Nailis; Wastri , Linda; Ardimen (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Language is a tool used to transmit knowledge. Language has a function as a medium or tool for thinking scientifically, but then a big problem arises and requires the help of philosophy. Language often cannot escape the confines of its users, language damage is usually caused by a lack of logical reasoning, which is called a lack of rationality. This type of research is qualitative research using library research methodology, which is a form of research that involves collecting data from scientific papers and collecting data that is bibliographical. Language is a verbal communication tool used in the process of scientific thinking, conveying the way of thought to others, both based on aqli. Using good language in thinking does not necessarily get the right conclusion, especially with bad language. A false premise will result in a wrong conclusion as well. This is inseparable from the role of language in learning and dissemination of knowledge as well as a medium for thinking and communicating with the same language. In the era of technology and globalization that we have encountered, the importance of understanding and developing a philosophy of science and language is very much a top priority in one's life. By understanding the relationship between the two, we can face challenges and improve our ability to communicate and interact with others.